Experimental Study on Dynamic Performance of Rock-Concrete Composite with Different Thickness Ratios. (11th May 2022) - Ping, Qi; Shen, Kaifan; Gao, Qi; Wang, Chen; Wang, Shuo; Wu, Yulin; Hu, Jing
Abstract : In order to study the influence of different thickness ratios on the mechanical properties of rock-concrete composite, a 50 mm diameter split Hopkinson pressure bar device (SHPB) was used to conduct impact loading tests on ϕ 50 mm × 50 mm cylindrical composite with sandstone thickness of 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 mm. The results show that with the increase of the proportion of rock in the composite, the dynamic compressive strength increases gradually, and the dynamic elastic modulus increases linearly. When the rock thickness increases, the average strain rate decreases and the peak strain decreases. In dynamic loading combination behind the rock specimen with concrete cushion, absorb energy decrease with the increase of rock accounted concrete; when the rock is 25 mm, total absorption energy reached its lowest point; when the thickness of the rock is greater than the thickness of concrete, concrete and adjacent parts of rock joint cushion absorb the energy into a rising trend. With the increase of the proportion of rock, the degree of fragmentation of the composite specimens decreases gradually, and the fragments are mostly concrete with smaller particle size, which is correlated with the dynamic compressive strength. The rock-concrete interface is a weak surface relative to the materials on both sides.